Issues to be discussed after ten years of the National Civil and Commercial Code validity (Nueva Epoca, 2025)
In this article the forfeiture of the option right and issues related to the succession of the surviving spouse will be discussed, ten years after the Civil and Commercial Code validity, with the aim of developing solutions to problematic situations.
Keywords: Inheritance; option right; forfeiture; surviving spouse; exclusion; community extinction